2020
DOI: 10.1029/2019jb018537
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Composition and Moho Variations of the Central and Eastern United States: Improving Resolution and Geologic Interpretation of EarthScope USArray Seismic Images Using Gravity

Abstract: EarthScope's USArray Transportable Array has shortcomings for the purpose of interpreting geologic features of wavelengths less than the Transportable Array station spacing, but these can be overcome by using higher spatial resolution gravity data. In this study, we exploit USArray receiver functions to reduce nonuniqueness in the interpretation of gravity anomalies. We model gravity anomalies from previously derived density variations of sedimentary basins, crustal Vp/Vs variation, Moho variation, and upper m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Pn tomography and Rayleigh wave dispersion and RF joint inversion studies (Buehler & Shearer, 2017; Shen & Ritzwoller, 2016) utilizing data from the USArray reveal a southeastward thinning of the crust across the SAM, a feature that has been pervasively observed by numerous passive or active source seismic investigations (see below) and is consistent with the seaward decrease in elevation and increase in Bouguer gravity anomalies (Zhang et al., 2020). Depending on the assumed crustal velocities, the estimated crustal thickness (H) can differ by up to 5 km in the SEUS (Buehler & Shearer, 2017).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Pn tomography and Rayleigh wave dispersion and RF joint inversion studies (Buehler & Shearer, 2017; Shen & Ritzwoller, 2016) utilizing data from the USArray reveal a southeastward thinning of the crust across the SAM, a feature that has been pervasively observed by numerous passive or active source seismic investigations (see below) and is consistent with the seaward decrease in elevation and increase in Bouguer gravity anomalies (Zhang et al., 2020). Depending on the assumed crustal velocities, the estimated crustal thickness (H) can differ by up to 5 km in the SEUS (Buehler & Shearer, 2017).…”
Section: Introductionsupporting
confidence: 59%
“…Crustal Vp/Vs (κ) values that are lower than the typical bulk crustal κ of 1.78 (Christensen, 1996) are observed in the Carolina Terrane and the Inner Piedmont (Hawman et al., 2012; Ma & Lowry, 2017; Parker et al., 2013; Zhang et al., 2020), and a crustal delamination/relamination hypothesis is proposed to explain the low κ measurements (Parker et al., 2013). Overall, the Appalachian Mountains show some of the highest crustal shear velocities in the continental United States (e.g., Porter et al., 2016; Shen & Ritzwoller, 2016), an observation that is consistent with the hypothesis that crustal densities increase beneath older mountain ranges (Fischer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The continental lithosphere, that is, the North American Craton (NAC), has remained stable for over 1.3 Ga despite subsequent reworking and deformation with the assembly and breakup of the Rodina and Pangaea supercontinents. In the past decade, seismic velocity structure of the crust and lithospheric mantle beneath the North American continent has been investigated by several techniques, including body wave tomography (Bollmann et al., 2019; Boyce et al., 2019; Chen et al., 2014; Porritt et al., 2014; Savage, 2021; Schmandt & Lin, 2014; Sigloch, 2011; H. Wang et al., 2019), receiver functions (L. Liu & Gao, 2018; Ma & Lowry, 2017; McGlannan & Gilbert, 2016; Yang et al., 2017; H. L. Zhang et al., 2020), full‐waveform inversion (Krischer et al., 2018), ambient noise tomography (Savage et al., 2017; Wu et al., 2020), surface wave tomography (Ekström, 2017; Pollitz & Mooney, 2016; Shen & Ritzwoller, 2016), and simultaneous inversion of receiver function, Rayleigh wave phase velocity and Bouguer gravity (Chai et al., 2022). These studies have provided a wealth of information on structural heterogeneities in the crust and lithosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the western and eastern margins of the Grenville Province and the boundary between the United States and Canadian portions of the Grenville Province are characterized by particularly fast and dense lower crust. Several previous studies have also suggested the presence of a relatively high‐velocity layer in the lower crust in parts of eastern North America, including northern New York (Hughes & Luetgert, 1992; Shalev et al., 1991), the southern Appalachians (Wagner et al., 2012), and the central and eastern United States in general (Schulte‐Pelkum et al., 2017; Zhang et al., 2020). Our new findings provide comprehensive maps of thickness, average velocity, and average density of the lowermost crust of eastern North America which, in turn, provide new constraints on its composition and evolution as briefly discussed below.…”
Section: Discussionmentioning
confidence: 92%